Reg3β is associated with cardiac inflammation and provides prognostic information in patients with acute coronary syndrome - Lörchner, Holger; Widera, Christian; Hou, Yunlong; Elsässer, Albrecht; Warnecke, Henning; Giannitsis, Evangelos; Hulot, Jean-Sebastien; Braun, Thomas; Wollert, Kai C.; Pöling, Jochen (International journal of cardiology, 2018)
Background - Regenerating islet-derived protein 3 beta (Reg3β) is a cardiomyocyte-derived chemokine for macrophages that is upregulated after myocardial infarction (MI) in mice. Here, we hypothesized that monitoring Reg3β expression might provide specific information on the degree of cardiac inflammation, which is a key determinant in disease progression and prognosis of patients with acute coronary syndrome (ACS). - Methods and results - The expression of Reg3β and other inflammatory markers including C-reactive protein (CRP) and myeloperoxidase (MPO) was measured by immunoblotting at serial time points in the hearts and serum of mice with acute MI. We identified a rapid increase of Reg3β, CRP and MPO expression in cardiac tissue and serum within the first 24h after MI. The expression of Reg3β peaked at day 4 and thereby paralleled the kinetic profile of the early immune-inflammatory response at sites of cardiac injury, which has been characterized by multicolor flow cytometry. In a retrospective analysis including 322 ACS patients and 117 apparently healthy individuals, we detected increased Reg3β serum concentrations in ACS patients on admission by ELISA. Multiple regression analysis revealed significant relationships between Reg3β and hs-CRP, age, diabetes and NT-proBNP in ACS. Moreover, elevated Reg3β levels on admission were associated with an increased risk of death independent of cardiovascular risk factors and hs-CRP. - Conclusions - Reg3β is a prognostic biomarker for ACS and is strongly associated with the intensity of cardiac inflammation. Accordingly, Reg3β may complement established strategies of acute risk assessment in the management of ACS.
Gesehen am 26.02.2020